2016
DOI: 10.1080/14737167.2016.1246960
|View full text |Cite
|
Sign up to set email alerts
|

How to prepare a systematic review of economic evaluations for informing evidence-based healthcare decisions: a five-step approach (part 1/3)

Abstract: Introduction: Systematic reviews of economic evaluations are useful for synthesizing economic evidence about health interventions and for informing evidence-based decisions. Areas covered: As there is no detailed description of the methods for performing a systematic review of economic evidence, this paper aims to provide an overview of state-of-the-art methodology. This is laid out in a 5-step approach, as follows: step 1) initiating a systematic review; step 2) identifying (full) economic evaluations; step 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
159
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(183 citation statements)
references
References 63 publications
1
159
0
14
Order By: Relevance
“…Conversely, a properly conducted systematic review of multiple economic analyses would often represent the highest level of economic evidence. Other approaches for the critical appraisal of model-based evidence are also available, including scoring systems for economic analyses 8 and guidelines for good modelling practices 5 and for the conduct of systematic reviews for economic evaluations 9 . Evidence in medicine that is based on mathematical modelling therefore varies with respect to its strengths and should affect clinical decisions only accordingly.…”
Section: Evidence In Medicine: Math Versus Biology!mentioning
confidence: 99%
“…Conversely, a properly conducted systematic review of multiple economic analyses would often represent the highest level of economic evidence. Other approaches for the critical appraisal of model-based evidence are also available, including scoring systems for economic analyses 8 and guidelines for good modelling practices 5 and for the conduct of systematic reviews for economic evaluations 9 . Evidence in medicine that is based on mathematical modelling therefore varies with respect to its strengths and should affect clinical decisions only accordingly.…”
Section: Evidence In Medicine: Math Versus Biology!mentioning
confidence: 99%
“…In this article, which focuses on Step 3 of the overall framework (see Figure 1 [1]), attention will be paid to data extraction, risk of bias assessment, and transferability when preparing a systematic literature review of economic evaluations (SR-EEs). Moreover, the article is also perfectly readable as a stand-alone read.…”
Section: Introductionmentioning
confidence: 99%
“…The term 'full EE' refers to the comparative analysis of alternative courses of action in terms of both costs (resource use) and consequences (outcomes and effects) [5]. Basically, there are two approaches to performing an EE study [7]: (1) an EE which is piggy-backed onto a clinical effectiveness study (e.g. a randomized controlled trial or observational study), often called a trial-based EE; and (2) a model-based EE, in which data from a wide range of sources (randomized controlled trials, observational studies, trial-based EEs, and other literature or reports) are combined using an economic model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though recommended, economic evaluations (EEs) are not routinely incorporated in clinical practice guidelines. 87 Studies investigating the uptake of HTA-studies in clinical practice found that this is generally limited, especially at the local level. 88,89 Until 2014, economic evidence was not incorporated into the Dutch clinical practice guidelines, which were based on scientific research (clinical trials) supplemented by the expertise of health care professionals and patients.…”
mentioning
confidence: 99%